2017
DOI: 10.1039/c7tb00328e
|View full text |Cite
|
Sign up to set email alerts
|

Oral delivery of curcumin via porous polymeric nanoparticles for effective ulcerative colitis therapy

Abstract: Oral drug delivery has been considered as a promising strategy for ulcerative colitis (UC) therapy. Here, an emulsion solvent evaporation technique was employed to prepare non-porous curcumin (CUR)-loaded polymeric nanoparticles (NPs) and porous CUR-loaded polymeric NPs in the absence or presence of ammonium bicarbonate. The resultant CUR-loaded NPs (non-porous NPs and porous NPs) had a desirable mean particle size of around 260 nm with a narrow size distribution, a uniform pore size distribution, slightly neg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…In particular, the least weight loss was found in the SNTs/Cur treated group and was followed by SNSs/Cur-, LNTs/Cur-, CSNTs/Cur-, BNSs/Cur-, and Cur-treated groups in increasing order. Besides the weight loss, the colon length shortening, epithelial destruction, and inflammatory cell infiltration were also important indicators for DSS-induced colitis in mice . Our results indicated that the colon length of DSS-induced UC mice was significantly shorter than that of the healthy group but a certain degree of recovery occurred after different Cur treatments (Figure B).…”
Section: Resultsmentioning
confidence: 66%
See 1 more Smart Citation
“…In particular, the least weight loss was found in the SNTs/Cur treated group and was followed by SNSs/Cur-, LNTs/Cur-, CSNTs/Cur-, BNSs/Cur-, and Cur-treated groups in increasing order. Besides the weight loss, the colon length shortening, epithelial destruction, and inflammatory cell infiltration were also important indicators for DSS-induced colitis in mice . Our results indicated that the colon length of DSS-induced UC mice was significantly shorter than that of the healthy group but a certain degree of recovery occurred after different Cur treatments (Figure B).…”
Section: Resultsmentioning
confidence: 66%
“…Besides the weight loss, the colon length shortening, epithelial destruction, and inflammatory cell infiltration were also important indicators for DSS-induced colitis in mice. 35 Our results indicated that the colon length of DSS-induced UC mice was significantly shorter than that of the healthy group but a certain degree of recovery occurred after different Cur treatments (Figure 5B). SNTs/Cur possessed the best recovery effect on colon length, and it is more obvious than Cur and other groups.…”
Section: ■ Results and Discussionmentioning
confidence: 66%
“…8 A) [ 87 ]. Recently, curcumin has been increasingly used in inhibiting oxidative stress and inflammation, in protecting cells in the central nervous system [ [87] , [88] , [89] ], and in treating chronic ulcers [ 90 , 91 ] and I/R injury [ 92 , 93 ].
Fig.
…”
Section: Ros-scavenging Nanomaterials That Promote Oxidative Damage Repair and Mechanisms Governing This Repairmentioning
confidence: 99%
“…Nanoparticle's shape, size distribution, and zeta potential play an essential role in regulating their release, cellular uptake, and in vivo bio distribution [23]. Therefore, designing the nanoparticles in terms of shape, size, and surface chemistry can maximize therapeutic efficacy.…”
Section: Synthesis and Characterization Of Porous And Nonporous Curcumin-loaded Dppsmentioning
confidence: 99%
“…Porous DPPs showed a high drug-loading amount compared to non-porous, which can be beneficial for an efficient drug delivery system (Table 1). The higher loading amount can be explained because of decomposition products of ammonium bicarbonate, which lowers the vapour pressure of organic solvents and accelerate the solidification of the polymeric matrix [23]. In vitro cytotoxicity of porous and non-porous DPPs at a given concentration (10-80 mg/ml).…”
Section: Synthesis and Characterization Of Porous And Nonporous Curcumin-loaded Dppsmentioning
confidence: 99%